An Analysis the Used of Code Swtching by the Teacher in Teaching English as Foreign Language at SMA N 3 Singaraja - Sudarmawan, Kadek Leo (Universitas Pendidikan Ganesha, 2022)
This study aimed at analyzing the types and functions of code-switching used by teachers in teaching English as a foreign language at SMA N 3 Singaraja. This study is a descriptive qualitative research. The subjects of this study are two English teachers who teach in 11th and 12th grades of language major. Data were collected using observation and interview methods. The instruments used in this study are observation sheets, video recorders, interview guide, and tape recorder. The results showed that there are three types of code-switching used by English teachers. They are intra-sentential code-switching (53%) by teacher 1 and (29%) by teacher 2, inter-sentential code-switching (41%) by teacher 1 and (45%) by teacher 2, and tag code-switching (6 %) by teacher 1 and (26%) by teacher 2. There are three functions of code-switching used by teachers; repetitive function (78%) by teacher 1 and (54%) by teacher 2, affective function (16%) by teacher 1 and (30%) by teacher 2, and topic switch (6%) by teacher 1 and (16%) by teacher 2.